Intrapulpal temperature variation during bleaching with various activation mechanisms - Sílvia Masae de Araujo Michida; Sheila Pestana Passos; Ângela Regina Kimie Marimoto; Márcia Carneiro Valera Garakis; Maria Amélia Máximo de Araújo (University of São Paulo, 2009)
OBJECTIVES: The aim of this study was to evaluate the intrapulpal temperature variation after bleaching treatment with 35% hydrogen peroxide using different sources of activation. MATERIAL AND METHODS: Twenty-four human teeth were sectioned in the mesiodistal direction providing 48 specimens, and were divided into 4 groups (n=12): (G1) Control - Bleaching gel without light activation, (G2) Bleaching gel + halogen light, (G3) Bleaching gel + LED, (G4) Bleaching gel + Nd:YAG Laser. The temperatures were recorded using a digital thermometer at 4 time points: before bleaching gel application, 1 min after bleaching gel application, during activation of the bleaching gel, and after the bleaching agent turned from a dark-red into a clear gel. Data were analyzed statistically by the Dunnet's test, ANOVA and Tukey's test (a=0.05). RESULTS: The mean intrapulpal temperature values (ºC) in the groups were: G1: 0.617 ± 0.41; G2: 1.800 ± 0.68; G3: 0.975 ± 0.51; and G4: 4.325 ± 1.09. The mean maximum temperature variation (MTV) values were: 1.5ºC (G1), 2.9ºC (G2), 1.7ºC (G3) and 6.9ºC (G4). When comparing the experimental groups to the control group, G3 was not statistically different from G1 (p>0.05), but G2 and G4 presented significantly higher (p<0.05) intrapulpal temperatures and MTV. The three experimental groups differed significantly (p<0.05) from each other. CONCLUSIONS: The Nd:YAG laser was the activation method that presented the highest values of intrapulpal temperature variation when compared with LED and halogen light. The group activated by LED light presented the lowest values of temperature variation, which were similar to that of the control group.